Improving Security and Reduce Overhead in Mobile Health Monitoring (International Journal of Engineering and Computer Science, 2015)
Cloud-assisted mobile health (mHealth) monitoring, which applies the prevailing mobile communications and cloud computing technologies to provide feedback decision support, has been considered as a revolutionary approach to improving the quality of healthcare service while lowering the healthcare cost. Unfortunately, it also poses a serious risk on both clients’ privacy and intellectual property of monitoring service providers, which could deter the wide adoption of mHealth technology. This paper is to provide better privacy and security in a mobile health monitoring system and also to protect the privacy of the involved parties and their data. Moreover, a newly proposed Diffie Hellman algorithm and Homomorphic encryption technique are adapted. Finally, the security and trust worthiness demonstrates the effectiveness of our proposed design. One service provider operates the encryption and decryption system while other providers operate the storage and application systems, according to the core concept of the proposed Health monitoring model. Our work further includes suggestions for multi-party Service- Level Agreement (SLA) suitable for use in the proposed Health monitoring model.